From Kitchen to Digital World: E-Business Implementation Strategies in the Culinary Sector Household Industry - Muhammad Muhammad; Andika Isma; Andi Naila Quin Azisah Alisyahbana (Indonesian Journal of Business and Entrepreneurship Research, 2023)
The purpose of this research is to find out the application of the culinary sector household industry and the positive impact in the application of e-business in Makassar City. The subject of this research is the community of Makassar City, which has a home industry that is still classified as a middle to lower class business. This type of research is descriptive qualitative using observation, interview, and documentation data collection. The results showed that the home industry is able to expand employment and provide broad economic opportunities to the community. Maintaining the existence of the home industry is that it must be able to compete, create new creativity and innovation, and increase capital to further develop its business in the present and in the future. home industry players pay more attention to marketed products and try to learn and add knowledge about doing business online and the Makassar City government must pay more attention to the home industry by providing training, both for production and marketing of the products produced.